Law Enforcement against Distance between Minimarkets in the Protection of Micro Businesses in Medan City Perspective of Maslahah Mursalah - Maharani, Maharani; Permata, Cahaya (Law Development Journal, 2024)
There are many minimarkets in Medan City that do not fulfill the provisions on minimarket distance. So that it is very impactful on micro businesses in Medan City. The purpose of this study is to determine the impact of law enforcement on minimarket distance on micro businesses in Medan City and to determine law enforcement related to minimarket distance in Medan City based on the perspective of Maslahah Mursalah. This type of research is empirical juridical, living case studies approach, conceptual, and statute approach. Data is collected through observation, interviews and document studies. Data is processed using qualitative methods with deductive thinking logic. The results show that the impact experienced by micro businesses with the presence of minimarkets makes micro businesses experience a decrease in turnover. With the mushrooming presence of minimarkets, the competitiveness of micro businesses increases in addition to competing with fellow micro businesses must also compete with minimarket businesses, what's more the distance between minimarket that are too close and even next to each other makes micro businesses experience a decrease in turnover in significance.